Key Pillars for FinTech and Cybersecurity: Array - Șcheau, Mircea Constantin; Rangu, Călin Mihail; Popescu, Florin Vasile; Leu, Daniel Mihail (Acta Universitatis Danubius. Œconomica, 2022)
The technological advancements of the last couple of years combined with the unique situation created by the Covid-19 pandemic made the customer more open to the digitalization of several financial services and procedures in order to further reduce the need for face-to-face interaction. The financial technology companies found themselves in the position to leverage advancements in fields such as data analytics and artificial intelligence as well as the new financial paradigm brought by blockchain technology thus making technological innovation a top priority to meet these new customer needs. As the tendency of the financial sector as a whole to further embrace digitalization becomes more apparent, so does the protection of customer data become more complex as cyber-attack vectors increase in complexity aided by an ever-expanding attack surface. We argue that the rapid pace in which technological advancements are adopted in the financial services sector must be accompanied by responsible cyber security policies and regulations enforced from both the technological and human standpoints. We will provide an overview on the pace in which cybercrime in the financial sector grew in intensity as FinTech moved towards an end-to-end approach, the most common cyber threats which affect the financial sector as well as why cyber threat management should not be limited to a reactionary approach.